Characteristics of phenotypic changes and genetic analysis of Drosophila melanogaster neurodegenerative mutation 3.5.8 - Щербакова, О. В.; Боднар, Л. С.; Горбулінська, С. М.; Черник, Я. І. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The locomotor activity of neurodegenerative mutants 3.5.8 has been studied. We have shown a significant reduction of run-length in mutants of different age, increase of grooming time and rest period with age. The study of mutants’ brain tissue revealed that neurodegenerative changes in these flies appeared in all parts of the brain on the 10th day after eclosion. According to the results, changes in mutants’ locomotor behavior appeared before the degenerative changes emergence in the brain and progressed with age. Mutation 3.5.8 was mapped in the region 63F1–64A4 of the third chromosome. Genes, localized in this region were analyzed and the candidates for further tests were selected.